Sodium Valproate Inhibits Small Cell Lung Cancer Tumor Growth on the Chicken Embryo Chorioallantoic Membrane and Reduces the p53 and EZH2 Expression - Lina Šlekienė; Donatas Stakišaitis; Ingrida Balnytė; Angelija Valančiūtė (SAGE Publishing, 2018)
The study aims to test the effect of different sodium valproate (NaVP) doses on small cell lung cancer NCI-H146 cells tumor in chicken embryo chorioallantoic membrane (CAM) model. Xenografts were investigated in the following groups: nontreated control and 5 groups treated with different NaVP doses (2, 3, 4, 6, and 8 mmol/L). Invasion of tumors into CAM in the nontreated group reached 76%. Tumors treated with 8 mmol/L NaVP doses significantly differed in tumor invasion frequency from the control and those treated with 2 mmol/L ( P < .01). The calculated probability of 50% tumor noninvasion into CAM was when tumors were treated with 4 mmol/L of NaVP. Number of p53-positive cells in tumors was significantly reduced when treated with NaVP doses from 3 to 8 mmol/L as compared with control; number of EZH2-positive cells in control significantly differed from all NaVP-treated groups. No differences in p53- and EZH2-positive cell numbers were found among 4, 6, and 8 mmol/L NaVP-treated groups. Invaded tumors had an increased N-cadherin and reduced E-cadherin expression. The results indicate the increasing NaVP dose to be able to inhibit tumors progression. Expression of p53 and EZH2 may be promising target markers of therapeutic efficacy evaluation.